Independent prognostic value of left atrial function by two-dimensional speckle tracking imaging in patients with non -ST-segment-elevation acute myocardial infarction. Issue 1 (December 2015) - Shao, Chunlai; Zhu, Jing; Chen, Jianchang; Xu, Weiting
Abstract Background The objective of this study is to evaluate left atrial(LA) function and its prognostic value by two-dimensional speckle tracking echocardiography (STE) in patients with non-ST-segment-elevation acute myocardial infarction (NSTEAMI). Methods Global longitudinal LA S/SR data obtained by 2D speckle imaging with automated software (Echo PAC, GE Medical). Results Clinical variables and angiographic, echocardiographic, and STE parameters were studied in 65 patients with NSTEAMI (51 males and 14 females; mean age of 60.7 ± 9.8 years) who underwent elective PCI. The final study population consisted of 51 individuals (43 males and 8 females; mean age of 62.9 ± 11.1 years) and a 12 ± 3 months follow-up was performed. A total of 22 combined cardiovascular events(20 patients) occurred. With the use of Univariable Cox regression, all parameters were evaluated in the prediction of cardiac events, ischemic events, and/or cardiac death. According to ROC analysis, baseline mean global left atrial SRs (ROC area 0.82, p = 0.001) and baseline mean global left atrial SRe (ROC area 0.68, p = 0.036) were the only predictive variables. Conclusions In patients with NSTEAMI, we found that the novel global strain parameter of left atrial function is a valuable predictor of combined cardiovascular events over conventional echocardiography and may therefore be an important clinical tool for risk stratification in the acute phase of NSTEAMI.